Nonlinear buckling and post-buckling of eccentrically stiffened functionally graded cylindrical shells surrounded by an elastic medium based on the first order shear deformation theory - Dung, Dao Van; Nga, Nguyen Thi (Vietnam Journal of Mechanics, 2013)
In this paper, the nonlinear buckling and post-buckling of an eccentrically stiffened cylindrical shell made of functionally graded materials, surrounded by an elastic medium and subjected to mechanical compressive loads and external pressures are investigated by an analytical approach. The cylindrical shells are reinforced by longitudinal and circumferential stiffeners. The material properties of cylindrical shells are graded in the thickness direction according to a volume fraction power-law distribution. The nonlinear stability equations for stiffened cylindrical shells are derived by using the first order shear deformation theory and smeared stiffeners technique. Closed-form expressions for determining the buckling load and load-deflection curves are obtained. The effectiveness of stiffeners in enhancing the stability of cylindrical shells is shown. The effects of volume fraction indexes, material properties, geometrical parameters and foundation parameters are analyzed in detail.